Pembuatan Sign System Sebagai Penanda Batas Antardusun di Desa Sambirejo, Kabupaten Jombang - Nabila Yasmin Widyana Damayanti; Yanda Bara Kusuma (FKIP, Universitas Palangka Raya, 2023)
Installing a sign system as a boundary marker between hamlets is one of the development efforts undertaken to improve the existing infrastructure in Sambirejo Village. It aims to direct visitors and provide information about the areas they enter, where each hamlet has its own tours and even MSME. The method of implementing the community service activity program carried out in the KKN-T MBKM UPN